Daily periodicity of labor in pregnant women in physiological and complicated pregnancy depending on the sex of the fetus - T. L. Botasheva; V. O. Andreeva; E. Yu. Lebedenko; A. D. Fabricant; A. V. Khloponina; E. V. Zheleznyakova; O. P. Zavodnov (Медицинский вестник Юга России, 2021)
Objective: the study aimed to reveal the daily periodicity of labor, the nature of melatonin metabolism, and the outcome of childbirth in women with a physiological and complicated pregnancy, depending on the sex of the fetus.Materials and methods: to study the chronophysiological characteristics of birth outcomes depending on fetal sex, 1 980 birth histories and stories of newborns were analyzed. The neonates were born between January 1 and December 31, 2016, in a maternity ward of the Federal State Budgetary Educational Institution of Higher Education “RostGMU” of the Ministry of Health of Russia. Melatonin production was identified by the level of urinary excretion of 6-sulfatoxymelatonin (6-SM) (its main metabolite) examining the morning portion of the urine of women by the ELISA method (at 8 am 3 ml of urine were collected in Eppendorf tube).Results: it was revealed that fetal sex modulated the activity of the central regulatory mechanisms responsible for the daily period functional processes in the female body and the initiation of labor. The largest number of spontaneous births by male fetuses occurred in the early evening before midnight when daily illumination was decreased, while the birth of girls was observed more often in the period from midnight to early morning. At the same time, mothers of boys had lower production of melatonin compared to that of girls’ mothers.Conclusions. The peculiarities of labor and birth complications associated with the sex of the fetus were identified.